Aplikasi Web Pemesanan Makanan Berbasis QR Code untuk Area Food Court - Falah, Muhammad Syahrul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The use of QR codes in food ordering systems is increasingly being used in restaurants or F&B (Food and Beverage) as a practical and efficient solution. This article discusses the planning of a web-based application prototype that integrates QR codes at each table in the food court, which allows buyers to access digital menus from various F&B tenants and place orders on the website application. This web application is also friendly to smartphones/mobile phones because it does not install additional applications and only uses a web browser and does not need to purchase hosting services because it uses the local/wi-fi network available at the food court. The purpose of this development is to improve the existing QR Code ordering system by adding table personalization features to the food court, ordering efficiency, and integration of all tenants in one platform.